2016
DOI: 10.1371/journal.pone.0160858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Form and Whole Grain Feeding on Gastrointestinal Weight and the Prevalence of Campylobacter jejuni in Broilers Orally Infected

Abstract: Two independent trials were carried out to evaluate the effect of feed form, whole wheat (WW) and oat hulls (OH) addition on gastrointestinal (GIT) weight and Campylobacter jejuni colonization in orally infected birds. In Trial 1, there were six treatments factorially arranged with two feed forms (mash vs pellets), and three levels of WW from 1-21/22-42d: 0/0, 7.5/15%, 15/30%. Broilers were allocated in cages (3 birds/cage, 12 cages/treatment). In Trial 2, there were three treatments: a mash diet, a mash diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Our previous study [ 8 ] showed that inclusion of 3% fine particle-sized OH has the potential to enhance growth performance and carcass weight of broiler chickens while OH fed as free-choice did not. Gracia et al [ 9 ] reported reduced cecal Campylobacter jejuni colonization when 5% OH was fed to broiler chickens in mash form compared to those fed in pelleted form. Hetland and Svihus [ 10 ] reported a faster feed passage with the inclusion of coarsely ground OH, but no effect of finely ground OH was found.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study [ 8 ] showed that inclusion of 3% fine particle-sized OH has the potential to enhance growth performance and carcass weight of broiler chickens while OH fed as free-choice did not. Gracia et al [ 9 ] reported reduced cecal Campylobacter jejuni colonization when 5% OH was fed to broiler chickens in mash form compared to those fed in pelleted form. Hetland and Svihus [ 10 ] reported a faster feed passage with the inclusion of coarsely ground OH, but no effect of finely ground OH was found.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are differences in gene expression and responsiveness to bacterial lipopolysaccharide between macrophages from males and females that have been attributed to the lack of dosage compensation of the genes on the Z chromosome, which includes the interferon cluster 41 . Apart from seasonality and sex, other non-genetic factors may explain the observed variation in Campylobacter colonisation, including strain variation 42 , the time and level of exposure relative to sampling 43 , coinfections 44 , variation in the gut microbiota 45,46 , and diet and feed intake 47,48 . Our results should be interpreted in the context of the limitations and advantages of field-based genome-wide association studies 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous data implied that offering a coarsely ground diet may hinder Salmonella proliferation [ 23 , 24 ]. Other research discussed the beneficial effect of whole wheat on other bacteria such as Clostridium perfringens [ 46 ] and Campylobacter jejuni [ 26 , 47 ] in broiler flocks. This could be explained on the basis that broilers fed a coarse ground diet showed better gizzard development than those animals fed a finely ground diet [ 23 , 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gracia et al [ 26 ] found that mash diets containing whole wheat and oat hull diet significantly reduced the caecal colonization of chickens with Campylobacter jejuni . Abadi et al [ 27 ] reported that feeding broilers on pellet coarse diets led to significantly lower caecal Clostridium counts.…”
Section: Introductionmentioning
confidence: 99%